Are You Looking for Madame or Maman? Role Playing the French Professor and the Mother in Academia - Rose, Sherri (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
Since becoming a parent, the last six years have been the most exhilarating and exhausting in the personal and professional spheres of my life. My heart was brimming with love following the birth of my first daughter while my brain was sending me stress signals to begin preparing for a tenure-track position in French at a small liberal arts college the next month. After the birth of my second daughter, and a year marked by injury, illness, and applying for tenure, I began to feel a growing sense of urgency to connect with other academic mothers. In this article, I share my personal journey as a female academic and mother with the aim of contributing to a wider discussion about maternal health and parenting in the academy. I reflect on the tensions originating from the roles I inhabit as both professor and mother—roles that have appeared to be at odds with one another from my job search through the tenure process. I have come to realize that I am happiest when I am able to see the various facets of my identity overlap in ways that invite knowledge and experience to nurture each other. I have sought to make my dual roles as professor and parent visible to my students by narrating various experiences raising my daughters in a bilingual home, by bringing my daughters regularly to campus, and by living in France together as a family while working with study abroad programs.